Italy and "Amsterdam Declaration" on patients' rights. - Bompiani, Adriano (Medicina e Morale, 1998)
This article is an analysis of the Declaration on the promotion of patients' rights in Europe, written by a group of experts under the patronage of the European Regional Office of the World Health Organization (WHO) during the meeting held in Amsterdam (28-30 March 1994). The WHO initiative shows the increasing interest of the European Union countries to make the internal regulations concerning the access to health services and their use by patients. In this way, not only the subjective rights of the human person, which by now have been codified, are recognized, but also the legitimate aspirations to improve the quality of assistance and human relationships in assistance. The analysis mentions the long list of "Declaration on man's rights" proclaimed in various international documents of high moral value, and the parallel declarations regarding the "patients' rights", and it then outlines the fundamental contents of the Amsterdam Declaration and evaluates them from a legal-ethical point of view. There is also an attempt to briefly study the analogies between this Amsterdam Declaration and the Charter of public health services which is the instrument that aims to put into practice article 14 of the parliamentary bill 502/1992 (and successive modifications and integrations) "Reorganization of the health regulations, in conformity with article 1 of the law of 23 October 1992 n. 421". Article 14, as it is known, concerns the "Citizen's rights". The declared principles in previously examined documents demand a firm adhesion to the foundations of "care ethics", viewed in light of personalistic ethical tradition.